GUILLAUME BRIÇONNET ET L'ÉVANGILE SELON SAINT JEAN - Veissière, Michel 1923-1996 (1995)
Après avoir donné une vue d'ensemble sur l'emploi de l'Écriture sainte par Guillaume Briçonnet, évêque de Meaux au début du XVIe s., et avoir présenté une première application pour les Psaumes (cf. Rev. Se. ph. th. 63 [1979] et 75 [1991]), il s'agit de montrer que cet évêque, très paulinien certes, a eu abondamment recours à S. Jean (230 mentions pour l'Évangile). De nombreux exemples, pris tout au long de cet Évangile, font apparaître ses choix, ses traductions, ses interprétations essentiellement spirituelles. After on overall view concerning the use of Holy Scripture by Guillaume Briçonnet, Bishop of Meaux at the beginning of the 16th century, and after a first concrete application to the Book of Psalms (cf. Rev. Se. ph. th. 63, 1979 and 75, 1991), the object is to show that this Bishop, however Paulinian he might have been, has abundantly resorted to St John (230 citations of the Gospel). Numerous examples, taken from throughout this Gospel, highlight his choices, his translations, his mainly spiritual interpretations.